Kinetic study of Fe silicates formation during iron corrosion in deaerated and alkaline Si-containing solutions at 50 °C. (February 2023) - Galai, Leila; Marchetti, Loïc; Godon, Nicole; Remazeilles, Céline; Refait, Philippe
Abstract: Kinetics of Fe silicates formation during iron corrosion in deaerated Si-containing solutions (Si concentrations varying from ≈0 to ≈110 mg L −1 ) were investigated for pH ranging from 7.5 to 10.1 at 50 °C. All Si consumption curves showed an induction period characteristic of nucleation and growth processes involved in Fe silicate formation. The experimental data obtained at pH≈ 7.5 and pH≈ 8.1 were correctly reproduced with a simplified model considering only the growth mechanism from dissolved species. This model however failed to reproduce the results obtained at pH≈ 10.1. Improving the description of nucleation processes seems necessary to achieve a more predictive modelling. Highlights: Fe silicate formation during Fe corrosion occurs by nucleation and growth processes. Fe silicate formation was modeled considering only the growth from dissolved species. The proposed model reproduces correctly the data collected at pH 7.5 and 8.1. This model fails to reproduce the results obtained at pH≈ 10.1.